(untitled) (Revista Contexto & Educação, 2025)
The thought of Mário Osório Marques has a significant impact on Physics teaching, promoting a critical and contextualized approach. His contributions highlight the need for an education that integrates theory with students’ sociocultural reality, opposing the traditional content-focused and decontextualized approach. Marques emphasizes three fundamental dimensions of pedagogy: hermeneutic, critical-dialectical, and epistemic-instrumental, which, when combined, enable a reflective and emancipatory teacher education. In Physics teaching, Marques proposes a methodology that values interdisciplinarity and problematization, making content more meaningful and applicable to students’ daily lives. At the same time, he warns against excessive mathematization and mechanization of teaching, advocating instead for a learning process that fosters inquiry and critical thinking. Furthermore, he stresses the importance of continuous teacher training, emphasizing that educators should act as mediators of knowledge, promoting students’ autonomy. Marques’ approach dialogues with Paulo Freire’s perspective but differs by emphasizing pedagogy as an epistemologically autonomous field. His ideas encourage innovative pedagogical practices that break away from traditional models and promote active student participation in the learning process. Thus, this article analyzes how Marques’ proposal represents a path to overcoming challenges in Physics teaching, bringing it closer to students’ real-life experiences and contributing to transformative education.